2008
DOI: 10.1590/s1517-86922008000500006
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da suplementação de creatina na captação de glicose em ratos submetidos ao exercício físico

Abstract: RESUMOEstudos recentes têm sugerido que a suplementação de creatina é capaz de modular a homeostase da glicose, aumentando sua captação pelos tecidos periféricos. O objetivo deste trabalho foi investigar o efeito da suplementação de creatina na tolerância à glicose e no conteúdo de glicogênio muscular e hepático em ratos submetidos ou não à atividade física por quatro e oito semanas. Ratos Wistar foram divididos em dois grupos: quatro e oito semanas de intervenção. Posteriormente, cada grupo foi subdividido em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…Similarly, Araujo et al [60] demonstrated that Wistar rats receiving creatine supplementation (diet supplemented with 13% for 7 days followed by 2% for 55 days) plus high-intensity exercise training exhibited a smaller area under the curve for glucose in response to an oral glucose challenge. On the other hand, Freire et al [61] did not show any effect of creatine (2% of creatine in drinking water for 8 weeks) plus swimming training on plasma glucose responses to an oral glucose tolerance test in Wistar rats. Likewise, Vaisy et al [62] did not demonstrate any benefits of creatine supplementation (diet enriched with 2.5% of creatine for 12 weeks) alone or in combination with exercise training on glucose homeostasis and muscular insulin sensitivity in Wistar rats with insulin resistance induced by a sucrose-rich cafeteria diet.…”
Section: Effects Of Creatine Supplementation Combined With Exercise Omentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, Araujo et al [60] demonstrated that Wistar rats receiving creatine supplementation (diet supplemented with 13% for 7 days followed by 2% for 55 days) plus high-intensity exercise training exhibited a smaller area under the curve for glucose in response to an oral glucose challenge. On the other hand, Freire et al [61] did not show any effect of creatine (2% of creatine in drinking water for 8 weeks) plus swimming training on plasma glucose responses to an oral glucose tolerance test in Wistar rats. Likewise, Vaisy et al [62] did not demonstrate any benefits of creatine supplementation (diet enriched with 2.5% of creatine for 12 weeks) alone or in combination with exercise training on glucose homeostasis and muscular insulin sensitivity in Wistar rats with insulin resistance induced by a sucrose-rich cafeteria diet.…”
Section: Effects Of Creatine Supplementation Combined With Exercise Omentioning
confidence: 92%
“…These conflicting results could be partially explained by the differences in creatine supplementation regimen and exercise types. For instance, both Freire et al [61] and Vaisy et al [62] used a single-phase creatine protocol throughout the entire intervention period, whereas others opted for a loading dose followed by a maintenance phase [62,63]. Training models also varied considerably with the use of treadmill [59,61,62] and swimming exercises [60], which precludes more direct comparisons concerning the exercise stimuli to which the animals were subjected.…”
Section: Effects Of Creatine Supplementation Combined With Exercise Omentioning
confidence: 99%
“…Furthermore, in aerobic exercise, literature displays differences regarding the possible effects of using creatine supplementation [2,5]. However, there are studies that have showed improvements in the use of creatine on aerobic performance, this would be done by the role of anaerobic energetic buffer generated by creatine supplementation [24,30]. It has been proposed that creatine and creatine phosphate (CP) act as messenger molecules between mitochondria and subcellular sites of production and hydrolysis of adenosine triphosphate (ATP) and thereby may aid aerobic activities [8,29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported increased rates of insulin secretion (Souza et al, 2006), increased expression of GLUT-4 receptors (Op'Teijnde et al, 2001;Souza et al, 2006) and increased intramuscular glycogen concentration after supplementation with creatine (Young et al, 2002). Although it is believed that creatine has a hypoglycemic effect, several authors failed to confirm hyperinsulinemia after the ingestion of creatine (Newman et al, 2003;Freire et al, 2008). With regard to the sporting environment, the literature suggests that creatine supplementation alters glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%